Study the effect of a Biosolvent preparation on the amount of salts in saline soils and antioxidant enzymes of cotton - Mamasolieva, Malika A; Gafurova, L. A; Hudoynazarov , I.A. (Journal of Soil Salinity and Water Quality, 2023)
Abstract Among abiotic stresses, soil salinization is a very serious environmental stress for plants, reducing yields by up to 20% on irrigated lands worldwide [1]. The study of the role of antioxidant enzymes in the activation of mechanisms of resistance to salinity and the scientific analysis of the influence of soil salts on the biochemical processes of plants serve as the basis for a quantitative and qualitative increase in plant productivity due to the activation of the immune system. Under salt stress, a number of biochemical processes are activated in the plant. It is important to scientifically substantiate the effect of salt stress on biochemical processes in the early stages of plant germination. The activities of peroxidase, polyphenol oxidase and phenylalanine ammonia-lease were significantly lower in roots and leaves of salt stressed in plants. The review considers the activity of antioxidant enzymes under salt stress. After washing the saline soil with the Biosolvent preparation, the activity of peroxidase, polyphenol oxidase and phenylalanine ammonia-lease increased in plants exposed to salt stress, which mitigated the negative impact of salt stress. Enzymatic activity was calculated based on Microsoft Excel at the rate of 1 mg/g in relation to the protein content. The activity of plant oxidoreductase enzymes in saline soil was studied using simple and experimental methods. For simple variants, water was used and the experiment was washed with Biosolvent.